1992
DOI: 10.3382/ps.0711259
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Viral Gene Distribution in Populations of Meat-Type Chickens

Abstract: The present study was designed to document the complexity of endogenous viral (ev) genes and seek evidence for their association with production traits in selected and control strains of meat-type chickens. Three populations were studied, each consisting of a control strain and one to three strains selected for various production traits. The ev genes were revealed by digesting genomic DNA with restriction enzymes and detecting DNA fragments on Southern blots using radioactive probes from nucleotide sequences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Strain (S) 90 has not been selected since 1955 (the 1950's population). From this parent population, S80 was selected for 14 generations for high 9-week BW and has been unselected since 1974 (Somes 1988, Sabour et al 1992. The BW of S80 chickens is 40% higher at 28 days and about 50% higher at 47 days (Chambers et al 1989), while abdominal fat of S80 birds at 47 days is 2·3-fold higher than that of unselected S90 chickens.…”
Section: Animalsmentioning
confidence: 99%
“…Strain (S) 90 has not been selected since 1955 (the 1950's population). From this parent population, S80 was selected for 14 generations for high 9-week BW and has been unselected since 1974 (Somes 1988, Sabour et al 1992. The BW of S80 chickens is 40% higher at 28 days and about 50% higher at 47 days (Chambers et al 1989), while abdominal fat of S80 birds at 47 days is 2·3-fold higher than that of unselected S90 chickens.…”
Section: Animalsmentioning
confidence: 99%
“…There is evidence to indicate slow feathering (SF) is a result of the incorporation of an endogenous retrovirus (EV) into the genome and that the feathering and ev21 genes are tightly linked (Bacon et al, 1988;Levin & Smith, 1990). Genes that affect the feathering rate have been identified in Leghorns (Levin & Smith, 1990), broilers (Sabour et al, 1992), turkeys (Asmundson & Abbott, 1961), and guinea fowl (Pal & Singh, 1997). There is evidence to suggest EV incorporations can adversely affect the immune competence of chickens.…”
Section: Introductionmentioning
confidence: 99%
“…However, gs antigen in albumen can also result from expression of endogenous viral (ev) genes, and high levels of the antigen have been found in eggs from meat-type chickens that were negative for exogenous virus (Ignjatovic, 1986;Spencer & Chambers, 1992). Sabour et al (1992) reported that meat chickens carry more of these ev genes than do egg-type stocks. However, in the present study, there was close agreement between tests for gs antigen in albumen and for virus in the eggs, suggesting that few eggs contained high levels of antigen of endogenous origin.…”
Section: Discussionmentioning
confidence: 99%